THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS MEDIATES THE RELATIONSHIP BETWEEN THE SOFTWARE OF INFORMATION TECHNOLOGY AND USER COMPETENCY TOWARDS THE QUALITY OF ACCOUNTING INFORMATION - Frisky, Nada Shafira; Rahmawati; Afrizon (Universitas Airlangga, 2023)
This research aims to examine the role of accounting information system effectiveness as a mediator in the relationship between information technology sophistication and user competence on the quality of accounting information. This research method uses a structural equation model with SmartPLS. Researchers distributed questionnaires to health facilities that have BPJS Health services in South Tangerang and Jakarta. The results of this research show that there is a significant relationship between the sophistication of information technology and user competence on the effectiveness of the accounting information system. The results of this research also show that the effectiveness of the accounting information system influences the quality of accounting information. The effectiveness of accounting information systems mediates the relationship between information technology sophistication and user competence on the quality of accounting information. This research provides a holistic model related to the quality of accounting information which is mediated by the effectiveness of the accounting information system.